2020
DOI: 10.1021/acssuschemeng.0c04398
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Reaction Mechanism and Active Sites of Metal–Organic Frameworks for Glucose Transformations in Water: Experimental and Theoretical Studies

Abstract: The catalytic performance of two different metalorganic frameworks, UiO-66 and MOF-808, containing Lewis acid active sites has been evaluated for the transformation of glucose in water, and compared with that of analogous Lewis acid Zr-Beta zeolite. While fructose is the main product obtained on Zr-Beta, the mannose production increases when using Zr-MOFs as catalysts. Kinetic studies reveal a lower activation energy barrier for glucose epimerization to mannose when using Zr-MOF catalysts (83-88 and 100 kJ/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…Density functional theory (DFT) calculations suggested that the activation energy of the 1,2-intramolecular hydride shift is similar among the three Zr-based materials. However, as for the 1,2-intramolecular carbon shift, the order of activation energy is UiO-66(Zr) < MOF-808(Zr) < < Zr-β zeolite, consistent with the corresponding selectivity order toward glucose [94].…”
Section: Glucose To Fructose/mannosesupporting
confidence: 72%
“…Density functional theory (DFT) calculations suggested that the activation energy of the 1,2-intramolecular hydride shift is similar among the three Zr-based materials. However, as for the 1,2-intramolecular carbon shift, the order of activation energy is UiO-66(Zr) < MOF-808(Zr) < < Zr-β zeolite, consistent with the corresponding selectivity order toward glucose [94].…”
Section: Glucose To Fructose/mannosesupporting
confidence: 72%
“…On the other hand, TMPO is a probe molecule that can diffuse through the MOF-808 pores and interact with both Lewis and Brønsted acid sites present in the metal-containing nodes, so the two types of acid sites can be distinguished by analysis of the 31 P MAS NMR spectra after TMPO adsorption. 41,45,46 Indeed, clear differences are observed between the 31 P MAS NMR spectra of the two TMPO-adsorbed Hf-MOF-808 samples (see Fig. 4 ).…”
Section: Resultsmentioning
confidence: 95%
“…38 For the simulation of NMR parameters, the isotropic absolute chemical shielding constants ( σ ) were obtained using the gauge including atomic orbitals (GIAO) approach 39,40 and the 31 P chemical shifts were calculated as δ iso ( 31 P) = σ ref − σ , using phosphoric acid as reference. To improve accuracy, all values were corrected with an equation obtained by fitting δ iso ( 31 P) values at 6-31G(d,p) level against δ iso ( 31 P) values at 6-311++G(d,p) level for a series of acid–base TMPO adducts, described in reference 41 .…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have focused on glucose isomerization employing protic solvents; however, in this work, we utilized a nonprotic solvent (γ-valerolactone). The reaction mechanism of glucose isomerization on Lewis acid sites has been studied by several authors, showing that intra- Please do not adjust margins Please do not adjust margins hydride transfer (C2 to C1) was the dominant reaction pathway in heterogeneous and homogenous systems 4,9,35,40 . The use of protic or nonprotic solvents has a strong effect on the balance of Lewis and Brønsted acid sites in the catalyst 27 ; thus, protic solvents generate Brønsted acid sites due to solvent molecules being ligated to metal atoms 27 .…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Furthermore, they have numerous modifiable compositions and can be easily functionalized, making them excellent and promising materials in heterogeneous catalysis applications, such as the oxidative desulfurization of fuels 19,20 , electrocatalysis [21][22][23][24] , gas adsorption and separation, hydrogen storage, drug delivery 25,26 and, in particular, catalytic and biomass valorization 10,[27][28][29][30][31][32] . A few studies have evaluated the catalytic activity of MOFs in glucose isomerization 10,[33][34][35] . But, the main effort has been done to modify MOFs (via metal clusters or organic ligands) to be applied for the one-pot synthesis of 5-HMF from glucose [36][37][38][39] .…”
Section: Introductionmentioning
confidence: 99%